ASSESSMENT OF THE CAPITAL ASSETS OF COMPANIES. A CASE OF «KOKAND MECHANICAL PLANT» JSC - Bunyod Usmonov (Scholar Express Journals, 2024)
The technical and theoretical components of determining a joint stock company's capital value through the discounted cash flow approach are discussed in this article. Also, the capital value of JSC «Kokand Mechanical plant» was evaluated using the discounted cash flows method. It also notes current issues and suggests solutions for them when utilizing the discounted cash flow approach to determine the joint stock company's capital worth.
Keywords: Discount Cash Flow; Terminal Value